Experiences and impact of moral injury in prisons - Victoria Williamson; Dominic Murphy; Danielle Lamb; Radha Kothari; Derek Tracy; Neil Greenberg (European Journal of Psychotraumatology)
Moral injury is the persistent mental or emotional distress resulting from events that challenge one’s moral beliefs. It is characterised by intense shame, guilt, worthlessness, disgust or anger and can contribute towards the development of serious mental disorders. The nature of working in prisons means that staff often face physically and psychologically challenging scenarios, and prison staff report high rates of mental ill-health and suicidal thoughts. Equally, detainees may be especially vulnerable to moral injury-related mental health difficulties having engaged in illicit actions and been found guilty by a jury of their peers as well as, in high profile cases, the court of public opinion. Despite this, there is an evidence gap about the extent of moral injury in both prison staff and detainee populations, and about how prison staff/detainees can be better supported. How struggling with moral injury may be linked to reoffending amongst detainees and burnout or resignations in prisons staff is currently unknown. In resource strapped prison settings, emerging treatments for moral injury-related mental health difficulties are unlikely to be appropriate or feasible. In this article, we highlight the contexts in which moral injury may arise; the unique challenges to treatment and support for moral injury in prison settings; and offer targeted recommendations for future research and clinical practice.